Examining the Antecedent Role of Movement Proficiency in Child Development: Study Protocol - Capio, Catherine M.; Lee, Kerry; Jones, Rachel A.; Masters, Rich S. W. (Frontiers in Psychology, 2021)
Background: Decades of research, largely from associational studies, show that the relationships of movement proficiency with the cognitive and social aspects of development are particularly strong in early childhood. Children who move proficiently tend to have better cognitive skills and social behaviors. However, the mechanisms that underpin these relationships remain unclear and research that explores causation is necessary. This study will explore the antecedent role of movement proficiency in the cognitive and social domains of child development, by examining whether a targeted movement skills training program facilitates improvements in cognitive and social skills. Methods: A group-randomized controlled trial will be conducted, implementing a fundamental movement skills training program in Hong Kong kindergartens. Participants will consist of children aged 3-5 years (N = 158) who will be randomly allocated by class to either a training or active control condition. The training program (10 weeks x 2 bouts) will be informed by an error-reduced approach to skills learning, which will involve careful design and manipulation of equipment and training environment to minimize practice errors. The active control condition will consist of typical movement activities implemented in the kindergartens in the context of the local curriculum guide. Outcomes will be measured using standardized tests of fundamental movement skills proficiency, executive functioning and social skills. Measurements will occur at baseline, mid-training, post-training, and follow-up. Latent variable longitudinal modeling will be used to analyze changes in the outcomes, with covariates that include sex, body composition, fine motor skills, and physical activity. Expected Results: The findings will subsequently be reported consistent with the Consolidated Standards of Reporting Trials (CONSORT) statement. Contributions to knowledge and understanding of child development are expected, through evidence of causal mechanisms surrounding the relationship of motor with cognitive and social development. The findings will also inform policy and practice related to early childhood development and education.